The Law of International Trade of Some European Socialist Countries and East-West Trade Relations - Jerzy Rajski (Washington University Law Quarterly, 1967)
The constant growth of the forces of production has led to a linking of the entire world and an unprecedented interdependence of the economies of various countries. Therefore the stabilization and further development of the world's economy cannot be envisaged without an ever-widening economic cooperation between all states belonging to different economic and social structures. International trade is the most important means of this cooperation because it constitutes an intermediary in the international circulation of goods. Hence the legal rules governing international trade transactions assume great importance. These rules are established by the laws of every country and also by international treaties and agreements.
Keywords: International trade